2016
DOI: 10.1111/lnc3.12184
|View full text |Cite
|
Sign up to set email alerts
|

L1 Grammar Instruction and Writing: Metalinguistic Activity as a Teaching and Research Focus

Abstract: Some authors have noted a lack of conceptual clarity in the field of L1 grammar instruction for writing.Here 'metalinguistic activity' is proposed as a concept that can contribute conceptual clarity by relating metalinguistic activity both to the ref lexivity that languages afford (i.e., using language to refer to language itself ) and to a sociocultural approach to languages (i.e., languages consist of semiotic tools that underpin our psychological development). I discuss how this notion is approached by Grup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
1
30
1
15
Order By: Relevance
“…This indicated that some pupils relied on a linear criterion, according to which any element immediately before the verb was a (personal) pronoun. These first results suggested a mismatch between declarative and procedural knowledge (see Fontich, 2016). Nonetheless, analysis of the interviews revealed that while some of the pupils relied quite heavily on some of the previous definitions of pronoun based on the ideas of substitution and reference, these ideas often appeared to be misleading.…”
Section:  Obstacles Related To Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicated that some pupils relied on a linear criterion, according to which any element immediately before the verb was a (personal) pronoun. These first results suggested a mismatch between declarative and procedural knowledge (see Fontich, 2016). Nonetheless, analysis of the interviews revealed that while some of the pupils relied quite heavily on some of the previous definitions of pronoun based on the ideas of substitution and reference, these ideas often appeared to be misleading.…”
Section:  Obstacles Related To Contentmentioning
confidence: 99%
“…Underpinning this idea is Vygotsky's (1962) claim that "A concept can become subject to consciousness and deliberate control only when it is a part of a system" (92). In the current debate on grammar instruction in the international arena, this issue is a focus of controversy (see Fontich &Camps, 2014, andFontich, 2016).…”
Section: Approaching the Process Of Grammar Learning: Raising Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on language acquisition have shown that the traditional teaching of grammar focused on the knowledge of language structures is far less valuable than metalinguistic awareness and conceptualization of the grammar system achieved by students through natural language activities such as writing, speaking, and reading (Fontich 2016;Milian 2005;Ribas, Fontich & Guasch 2014;Unsworth 2002;Uppstad 2006). The above conclusions advocate a claim that the ability to think deeply about the language and how it is used is far more significant than a mere reproduction of grammar content presented by a teacher, and also than the teaching of a series of grammar rules.…”
mentioning
confidence: 99%